2012
DOI: 10.5056/jnm.2012.18.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Does Acupuncture Therapy Alter Activation of Neural Pathway for Pain Perception in Irritable Bowel Syndrome?: A Comparative Study of True and Sham Acupuncture Using Functional Magnetic Resonance Imaging

Abstract: Background/AimsPatients with irritable bowel syndrome (IBS) are characterized by abnormal central processing with altered brain activation in response to visceral nociceptive signals. The effect of electroacupuncture (EA) on IBS patients is unclear. The study is set to study the effect of EA on brain activation during noxious rectal distension in IBS patients using a randomized sham-controlled model.MethodsThirty IBS-diarrhea patients were randomized to true electroacupuncture or sham acupuncture. Functional M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 38 publications
0
74
1
2
Order By: Relevance
“…(28) By contrast, acupuncture and Mox can effectively treat IBS through regulation of brain, gastrointestinal tract and other channels. (14)(15)(16)(17)(18)(19)(20)29) In this trial, we observed that 5-HT and 5-HT3R expressions in colon tissue of D-IBS patients before treatment were higher than healthy volunteers. After Mox and EA treatment, both 5-HT and 5-HT3R expressions in colon tissue were reduced, and abdominal pain, bloating or discomfort, as well as defecation frequency and emergency in patients of both groups were relieved.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…(28) By contrast, acupuncture and Mox can effectively treat IBS through regulation of brain, gastrointestinal tract and other channels. (14)(15)(16)(17)(18)(19)(20)29) In this trial, we observed that 5-HT and 5-HT3R expressions in colon tissue of D-IBS patients before treatment were higher than healthy volunteers. After Mox and EA treatment, both 5-HT and 5-HT3R expressions in colon tissue were reduced, and abdominal pain, bloating or discomfort, as well as defecation frequency and emergency in patients of both groups were relieved.…”
Section: Discussionmentioning
confidence: 84%
“…(12,13) In China and some other countries, electroacupuncture (EA) and moxibustion (Mox) have been applied as effective treatments for diarrhea-or constipationpredominant IBS. (14)(15)(16)(17) Mox is observed for the treatment of diarrhea-predominant IBS (D-IBS) or improvement of the main symptoms of diarrhea, (18,19) and EA has been widely recognized for the treatment of constipation-predominant IBS or functional constipation. (20) This study further validates whether EA and Mox have different effects on patients with D-IBS through the comparison and evaluation of the effects of these two treatments on the primary gastrointestinal symptoms, psychological symptoms, expressions of 5-HT, 5-HT3R and 5-HT4R in the colon tissue, and the excitation in the relevant functional areas of the brain in patients with D-IBS.…”
mentioning
confidence: 99%
“…The brain activity during acupuncture suggested the modulation of serotonin pathway at insula and the higher cortical regulation of affection as potential neural mechanisms of acupuncture treatment. 34 Furthermore, correlation analysis between fMRI data and psychological indices such as anxiety and depression may demonstrate the influence of the psychological state on patients. 28,35 When interpreting the fMRI results on interventions, the blinding issue, changes of symptoms, co-morbidities, quality of life, non-specific effect, and placebo response should also be taken into consideration carefully.…”
Section: Interpreting Functional Magnetic Resonance Imaging Results Imentioning
confidence: 99%
“… d'une part, en imagerie l'activation préférentielle de certaines zones corticales lors de la stimulation des acupoints correspondant à ces pathologies, à la fois chez des sujets souffrant d'intestin irritable et des sujets sains ;c es zones sont le cortex cingulaire antérieur,l 'insula, et le cortex préfontal ;  d'autre part, une liaison significativee ntre l'amélioration clinique sous acupuncture et l'évolution vers la normalité de l'IRM fonctionnelle par comparaison avecd es sujets témoins [22,23,24]. De plus, Chu [24] étudiant la sensibilité rectale sous distension par ballonnet, montre la diminution de l'hypersensibilitéàla distension sous acupuncture avec corrélation avecl es données de l'IRMf.…”
Section: Recherche Chez L'hommeunclassified
“…De plus, Chu [24] étudiant la sensibilité rectale sous distension par ballonnet, montre la diminution de l'hypersensibilitéàla distension sous acupuncture avec corrélation avecl es données de l'IRMf.…”
Section: Recherche Chez L'hommeunclassified